An Educational Glance into the Future: Holodeck as a Future Enacted Narrative Learning Technology - Tiina Kymäläinen (Journal of universal computer science, 2019)
his article describes how the fictional concept of Holodeck can be seen as a future immersive learning technology, as well as a new medium for future enacted, narrative experiences. In essence, the article illustrates how this fictional media has been recently studied within the art education context; particularly with the emphasis on how the medium has been considered through the holonovel writing activity. At first, the literature review presents earlier Holodeck-related research, innovation and applications, which, subsequently, provide important terminology for the holonovel writing process. The terminology includes the setup, important stakeholders and those critical units and entities that are needed for defining the pre-conditions for the Holodeck. Thereafter, the article introduces content of the holonovel course and the creation process for such holonovels that take the form of science fiction prototypes. Finally, the article presents some student-created examples of holonovels that employ the Holodeck for educational and pedagogical purposes.